Swaddling Infants - Clark, Madison A.; Gunter, Caitlyn D.; Nelson, Laken M.; Rehberg, Bailey R.; Williams, Tal N. (My University, 2020)
Swaddling infants has been known to provide them comfort when transitioning from the womb to the world. There has been an ongoing debate of whether or not this intervention is as helpful as we have known it to be in the past. We have performed a systematic literature review to answer the question: In infants, what are the effects of swaddling on sleeping practices and comfort? We studied peer-reviewed articles and have gathered information related to answering our research question. Some research has shown that swaddling is no longer in use due to the risks it presents with. We developed a practice protocol to address the effect that swaddling has on infants. The impact of this research is to determine if swaddling is beneficial regarding the sleeping practices and comfort of infants.